Blended Learning in Language Teaching: A Review - Noviarini, Tiara (Peneliti.net, 2024)
In recent years, mixed learning has become a flexible educational method with the changing needs of the times by blending both face-to-face and online learning activities. The purpose of this study was to examine trends and research findings regarding blended learning in language learning. For this purpose, a database of highly reputable publishers was reviewed from 2015-2020. A systematic review was used as the methodology for this study. Articles were analyzed using the content analysis method. The research findings show that blended learning in language learning consists of various skills that can be improved in language competence. The research methods most often used in language learning are found in quantitative and mixed methods. In language learning, most of the blended learning classes are applied in linguistics learning. Besides, research that reviews the effectiveness of blended learning methods mostly shows the many advantages of blended learning methods to improve student's abilities in language learning.